The effectiveness of successful maintenance management in public hospital building - Mardhiah Farhana Omar (School of Environmental Engineering, 2017)
The scope will focus on maintenance management in the hospital building. This study will focus on government hospitals and maintenance services include civil engineering service, mechanical equipment service, electrical and telecommunication. The total of hospital building is many and it is troublesome to gather the data in a short period of time and with a limited budget. Therefore, this study is expected to be implemented in the maintenance management for the hospital building in this country.